PTU-029 A novel MRI protocol to examine haemodynamic compartments in compensated liver cirrhosis. (28th May 2012) - Cox, E F; Ghezzi, A; Patel, M; Jackson, A; Costigan, C; James, M W; Ryder, S D; Gowland, P A; Aithal, G P; Francis, S T; Guha, I N
Abstract : Introduction: The hyperdynamic circulation in cirrhosis results from changes in the splanchnic, systemic, cardiac and renal compartments; it underpins the clinical consequences of portal hypertension. We present a novel MRI protocol that provides non-invasive measurement of these different haemodynamic compartments in a single assessment. Phase contrast (PC) MRI is a validated technique for the measurement of velocity (in cm/s), area, and hence flux (=velocity*area (in ml/s)) in a given vessel. 1 Here, we use PC-MRI, together with MR measures of cardiac function, to assess haemodynamics in early, compensated cirrhosis and matched healthy volunteers. Methods: Patients were studied from a prospective, longitudinal study of compensated cirrhosis (CC) (Child Pugh A) with age and sex matched healthy volunteers (HV). 20 CC patients (13M/7F, age 57±1 y (mean ± SEM), aetiology 2 ALD, 1 HBV, 7 HCV, 3 NAFLD, 1 PBC, 1 Haemochromatosis, MELD 0–10.6) and 20 HV: 13M/7F, age 57±2 y were included. PC-MRI data were collected for the superior mesenteric (SMA), splenic (SA), hepatic (HA), and renal (RA) artery and portal vein (PV). 15 phases were acquired across the cardiac cycle to calculate the mean area, velocity and flux for each vessel. Cardiac MR consisted of short axis cine images to measure left ventricular ejection fraction (EF) and PC-MRI of the aorta. All data were collected within 20 min, with images acquired during short breath-holding (12–15 s). Results: In CC, the portal vein was dilated and had a reduction in velocity compared to the HV group (Abstract PTU-029 figure 1A ). The SMA (Abstract PTU-029 figure 1B) and SA, showed vasodilation and increased flow velocity, and a resulting increase in flux in patients with CC compared to the HV. There was a trend for a reduction in RA velocity (Abstract PTU-029 figure 1C) and an increase in HA velocity in CC. The ejection fraction was significantly higher in CC compared with the HV (Abstract PTU-029 figure 1D). There was no change in aortic flux, velocity or area with CC. Conclusion: Using a non-invasive MRI protocol, we have measured haemodynamics in four compartments contemporaneously in cirrhosis. The detection of significant changes in early cirrhosis, suggests this technique has potential to (a) study the evolution of portal hypertension with accompanying changes in splanchnic, renal and systemic circulation as well as (b) assess the haemodynamic response to novel therapeutic agents in cirrhosis. Competing interests: None declared. Reference: 1. Debatin JF . Abdom Imaging 1998;23 :485–95.